Molecular Mechanisms of Disease Pathogenesis Differ in Krabbe Disease Variants - Spratley, Samantha J. (Traffic, 2016)
Krabbe disease is a severe, fatal neurodegenerative disorder caused by defects in the lysosomal enzyme galactocerebrosidase (GALC). The correct targeting of GALC to the lysosome is essential for the degradation of glycosphingolipids including the primary lipid component of myelin. Over 100 different mutations have been identified in GALC that cause Krabbe disease but the mechanisms by which they cause disease remain unclear. We have generated monoclonal antibodies against full‐length human GALC and used these to monitor the trafficking and processing of GALC variants in cell‐based assays and by immunofluorescence microscopy. Striking differences in the secretion, processing and endosomal targeting of GALC variants allows the classification of these into distinct categories. A subset of GALC variants are not secreted by cells, not proteolytically processed, and remain trapped in the ER; these are likely to cause disease due to protein misfolding and should be targeted for pharmacological chaperone therapies. Other GALC variants can be correctly secreted by cells and cause disease due to catalytic defects in the enzyme active site, inappropriate post‐translational modification or a potential inability to bind essential cofactors. The classification of disease pathogenesis presented here provides a molecular framework for appropriate targeting of future Krabbe disease therapies. [Image: see text]